Globalization and legal cultures : Oñati Summer Course 1997 - Feest, Johannes ((Oñati Papers ;)
Contiene los trabajos: Legal culture on every conceptual level. La cultura legal: cómo se mide. Escándalos de corrupción y cultura jurídico política: un análisis desde Venezuela. The gatt of law and democracy: (mis)trusting the global reform of courts. The influence of dispute resolution on globalization: the polítical economy of legal models. Globalización y sistema penal en América Latina: de la seguridad nacional a la urbana. Le droit comme instrument de mondialisation.